A Model of Modern Islamic Education: MAN Insan Cendekia in Indonesia and Imam-Hatip High School in Turkey - Junaedi, Dedi; Fikri, Ishom Fuadi; Kusaeri, Kusaeri; Rusydiyah, Evi Fatimatur (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2023)
Madrasahs in the perception of some people are still seen as lowquality education. However, the existence of Madrasah Aliyah Negeri Insan Cendekia (MAN IC) in Indonesia and the Imam-Hatip School (IHS) in Turkey seeks to ward off this perception through institutional modernization. This study aims to reveal the model of Islamic education in MAN IC and IHS by comparing the two in several aspects. Where this study uses the method of literature review through data sourced from scientific articles, both indexed by Scopus and Sinta 1-2. The results of this study indicate that MAN IC and HIS: 1) are modern Islamic educational institutions under the auspices of government; 2) aims to produce graduates who are equally qualified, both in the realm of religion and science; 3) having a curriculum that combines Islamic religious education, culture, science, and technology; 4) have teachers who are professional and competent in their respective fields; 5) using the mechanism of the entrance selection test for prospective students; 6) implementing a boarding program with excellent standard facilities for students so they can focus on studying and take part in intensive international language training. Based on the results of this study that MAN IC and Imam Hatip are modern Islamic Education models that are quite ideal, especially at the higher secondary level, so it is expected to be a reference material for Islamic education practitioners in Indonesia in this modern era.